PENGARUH TUGAS TERHADAP SIKAP TANGGUNG JAWAB ANAK 5-6 TAHUN TK MIFTAHUL JANNAH SIAK - Mita Triwati (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2020)
The purpose of this study is to improve children's responsibility attitudes through the method of assigning tasks in Miftahul Jannah Kindergarten, Minas District, Siak Regency. This research uses quantitative methods that are analyzed by experiment with quasi experiment methods. The test used is the parametric Paired Sample T-Test. The two different test models are used to analyze the pre-post or before and after research models. A different test was used to evaluate the treatment (treatment) in Miftahul Jannah Kindergarten, Minas District, Siak Regency, totaling 20 children. The results of this study are that there is an influence of the use of the assignment method to the ability of the attitude of responsibility of children aged 5-6 years in Miftahul Jannah Kindergarten, Minas District, Siak Regency. If the pretest averaged 12.7% posttest to 28.9%. Thus an increase occurred, so it can be concluded that the use of the assignment method can improve the ability of the attitude of responsibility of children aged 5-6 years at Miftahul Jannah Kindergarten, Minas District, Siak Regency. it is known that the use of the assignment method has an effect on the ability of the attitude of responsibility of children aged 5-6 years in Miftahul Jannah Kindergarten, Minas District, Siak Regency.